Integrated Photo‐Responsive Batteries for Solar Energy Harnessing: Recent Advances, Challenges, and Opportunities. Issue 4 (1st April 2020) - Fang, Zhengsong; Hu, Xuanhe; Yu, Dingshan
Abstract: Invited for this month's cover is the group of Prof. Dingshan Yu from Sun Yat‐sen University, China. The Front Cover shows an integrated photo‐responsive battery with the simplest two‐electrode configuration powering a vehicle under light illumination. The Taiji diagram shows the working principle of this device, which combines photoexcited electrons (e ‐ ) and/or holes (h + ) with various redox species of the batteries during charging and/or discharging processes to realize the harnessing of solar energy. Read the full text of the Minireview at 10.1002/cplu.201900608 . Abstract : "Although great progress has been made in the field of integrated photo‐responsive batteries, several main challenges such as low overall energy efficiency, poor stability, and compatibility of different modules remain to be resolved. Exploring advanced and compatible electrolyte and electrode materials with good photoelectric conversion capability is critically important to the overall performance of these systems." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.201900608 ).